EFEKTIVITAS KOMUNIKASI ANTAR PRIBADI TERHADAP KEPUASAN MAHASISWA DALAM KEGIATAN PEMBELAJARAN TATAP MUKA DI ERA PANDEMI PADA MAHASISWA FISIP UIN RADEN FATAH PALEMBANG - Sepriadi Saputra; Gitra Astrid (Professional: Jurnal Komunikasi dan Administrasi Publik, 2021)
The Covid-19 pandemic has been around for a very long time. Detected in December 2012 in Wuhan and entered Indonesia in March 2019, many things must be totally changed in social life. One of the hardest hit areas is education. Changes in behavior in carrying out education are felt to be difficult for all students, especially in Indonesia.This study reveals the effectiveness of interpersonal communication on student satisfaction in face-to-face learning activities in the Pandemic Era for students of FISIP UIN Raden Fatah Palembang. Researchers use Social Presence Theory to determine the effectiveness of interpersonal communication in face-to-face learning in the Pandemic era. Students who carry out face-to-face activities feel an increased affective association, instructor investment, knowledge and experience, interaction intensity, and community cohesion. In the five indicators in the Social Presence Theory, it is known that students of Fisip UIN Raden Fatah Palembang feel that learning activities are more effective and fun than online learning methods. This study shows that face-to-face learning activities should not be eliminated, because humans need interaction in socializing in order to grow the same desires and goals. Online learning is not a bad thing, and it really helps learning, but in the context of learning, internet connection and assistance from sharing media and sophisticated communication tools cannot be separated from learning activities done face to face.